(3OjhGf GdWZQGFjs - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3bGd jeOM GdSdWGf GdeYXe GdSYjO eMeO Hf edc TGg(B: (3dLdGd bOQc JNVY GdCbOGQ hHjejf LOc jMce GdebOGQ s
(3BNQgG (B:s
(3aYGLrdg HYRd Ch HbJd hMj, agj YGOJc GdLejdI hcGjrd TDeg UGYG HUGY hef jZdH aEf dg GdaVjdI hgPG BNQ eG ohLO ef TYQ eDjO GdOjf GdWZQGfj s
(3fSNI KGdKIs
(3hYdjgG oeWGdYI HJGQjN (B1060(3g````s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B147 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B798s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs